Financial action task force and the fight against money laundering and the financing of terrorism: Quo vadimus?. Issue 3 (20th January 2020) - Pavlidis, Georgios
Abstract : Purpose: Thirty years after its creation, the Financial Action Task Force (FATF) has become a prime example of a norm-building process that transcends the traditional avenues of public international law, while compelling a high level of compliance and assuring quick adaptation to norms and practices that better address money laundering and the financing of terrorism in their evolving form. On the occasion of FATF's 30th anniversary, this paper aims to revisit the unique characteristics of FATF and the factors behind FATF's success as standard-setter and as implementation-reviewer in the anti-money laundering (AML)/CFT context. Design/methodology/approach: This paper draws on primary sources of law, legal scholarship, reports and other open source data to analyse the FATF norm-building process and the factors behind its success. Findings: Thirty years after its creation, the FATF has established itself as the key standard-setter, implementation-reviewer and force for reform in the AML/CFT context. Though the FATF norm-building process has been very successful, owing to its flexibility, adaptability and expansiveness, significant challenges lay ahead due to the evolving nature of money laundering and financing of terrorism. Originality/value: This is a comprehensive study examining the achievements, impact, strengths and weaknesses of the FATF norm-building process on the occasion of the organisation's 30th anniversary.